Results of an Academic, Health Care Worksite Weight Loss Contest for Southeastern Americans: Scale Back Alabama 2011-2013. (April 2015) - Breaux-Shropshire, Tonya L.; Whitt, Lauren; Oster, Robert A.; Lewis, Dwight; Shropshire, Toneyell S.; Calhoun, David A.
Few studies have assessed the effectiveness of competitive incentivized worksite weight loss programs. Scale Back Alabama (SBA) is a free, state-supported program designed to promote weight loss among overweight and obese citizens. The purpose of this manuscript is to describe the design and preliminary findings of SBA as a worksite intervention among employees at a collegiate institution and university hospital. In teams of 4 employees, SBA participants volunteered to engage in a 10-week competitive weight loss contest; both teams and individuals who lost significant weight were eligible for randomly drawn cash incentives. Trained staff objectively measured participants' weight before and at the conclusion of the contest. Preliminary analyses suggest that SBA as a worksite program can promote weight loss among employees, but future analyses are warranted to understand the context of these findings and determine if current results are confounded by unmeasured factors.